Pengaruh Biaya, Produktivitas Aktiva dan Struktur Modal dalam Meningkatkan Profitabilitas Perusahaan - Muhammad Yusuf (Binus Business Review, 2010)
This study examined the effect of cost, productivity of assets and capital structure of an automotive company's profitability. This study focuses on the productivity of assets which include factors such as operating leverage, sales, inventory turnover, net working capital, liquidity, receivable collection, fixed asset ratio, and total asset turnover. Capital Structure includes the degree of financial leverage. Profitability factor in this study includes operating margin, return on assets and return on equity. Sample used are 45 automotive industry companies who have registered and still active until December 31, 2009. The statistical methods used in this research are classical assumption test, f test and t test. This study indicates that inventory turns, liquidity, receivable collections and, the ratio of fixed assets have a negative outcome to the total asset turnover, while net working capital has a positive outcome. Operating margin and total asset turnover both have positive values that have an impact on return on assets. Capital structure and degree of operating leverage both have negative results on the turnover of capital, while return on assets have positive results.